Gender Equality and Islamic Education: A Harmonious Connection - Muqarramah Sulaiman Kurdi (STIKes Ibnu Sina Ajibarang, 2023)
This article investigates the intricate intersection of gender equality and Islamic education, presenting an in-depth analysis of the debates, paradoxes, and potential solutions within this multifaceted domain. Employing a qualitative research approach centered on library research and descriptive analysis, the study aims to offer a comprehensive, objective, systematic, analytical, and critical examination of the intricate relationship between gender equality and Islamic education. The findings and discussions underscore the imperative to reconcile tradition and progress in the reformation of Islamic education for achieving gender equality. The study advocates for the promotion of critical thinking and nuanced interpretation of religious texts, ensuring equitable access to education for women, challenging entrenched patriarchal norms, integrating women into decision-making processes and leadership roles, mobilizing men as advocates for gender equality, and fostering collaboration between Islamic education institutions and women's organizations. Moreover, the research addresses persistent challenges hindering gender equality in Muslim education, such as deep-rooted patriarchal attitudes, practices, and barriers to educational access.